Characterization of microstructures and age hardening of Fe 1-2xAlxVx alloys - Ferreirós, Pedro Antonio (2014)
The Fe-rich corner of the Fe-Al-V system has shown phase separation into disordered A2 and ordered L21 phases. In a former work we model this ordering reaction by using ab-initio thermodynamics. The approach is now employed to suggest the Fe1-2xAlxVx alloys in order to reduce the Al content by increasing the addition of vanadium looking for a better ductility of the solid solution which can be afterwards strengthened by coherent L21 precipitates. Four alloys with compositions in the range 0.08 < X < 0.15 were studied. The phase transition temperatures and microstructures of the alloys were characterized by differential scanning calorimetry (DSC) and transmission electron microscopy (TEM), respectively. The region (A2 + L21) occurs for 0.10 < X < 0.15 up to maximum temperature of 720 C, higher temperatures causes the appearance of (A2 + B2), B2 and (B2 + L21) regions. The microstructure in the (A2 + L21) region consists of nanosized precipitates of L21 phase in A2 matrix which morphology evolutes with temperature and ageing time. The hardness values, measured at room temperature, for the alloys with X < 0.125 and ageing temperature between 650 and 700 C are comparable to those obtained with other Fe-Al based alloys.